1994
DOI: 10.1093/carcin/15.5.979
|View full text |Cite
|
Sign up to set email alerts
|

A 32P-postlabeling method for simultaneous detection and quantification of exocyclic etheno and propano adducts in DNA

Abstract: A 32P-postlabeling method is described that specifically detects and quantifies the 1,N2-propanodeoxyguanosine adducts derived from acrolein (AdG) and crotonaldehyde (CdG) and 1,N2-ethenodeoxyguanosine (EdG) in DNA. These exocyclic adducts are potential DNA lesions caused by exposure to enals as environmental pollutants and as endogenous compounds. This method was developed with the use of the synthetic adduct standards of these exocyclic adducts. The assay relies on HPLC for adduct enrichment prior to labelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 0 publications
1
30
0
Order By: Relevance
“…Structural constraints in genomic DNA and chromatin structure may hinder formation of Acr-dG 1 and 2 adduct isomers. Our results are consistent with well established findings that Acr can react directly without metabolic activation with guanine residues in DNA to produce exocyclic propanodeoxyguanosine DNA adducts (12,13,(16)(17)(18).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Structural constraints in genomic DNA and chromatin structure may hinder formation of Acr-dG 1 and 2 adduct isomers. Our results are consistent with well established findings that Acr can react directly without metabolic activation with guanine residues in DNA to produce exocyclic propanodeoxyguanosine DNA adducts (12,13,(16)(17)(18).…”
Section: Resultssupporting
confidence: 92%
“…Acr has been shown to interact with nucleophiles, including DNA and proteins in cells (32). Unlike PAHs, where only metabolically activated forms can form adducts with DNA, Acr can directly interact with DNA and form DNA adducts (18,23). Similar to PAH-DNA adducts, Acr-DNA adducts induce mainly G:C-to-T:A transversion mutations (10,(33)(34)(35), the major type of mutations found in the p53 gene in CS-related lung cancer.…”
Section: Acr-dg Adducts Induce G-to-t Transversion Mutations In Humanmentioning
confidence: 99%
“…Acr, micrococcal nuclease, dG, dG 3′-monophosphate, 2-deoxyadenosine 3′-monophosphate, 2-deoxycytidine 3′-monophosphate, thymidine 3′-monophosphate were obtained from SigmaAldrich Co. (ST. Louis, MO), Acr-dG 3′-or 5′-monophosphate was prepared as previously described, and the identities of these standards were established by their UV spectra and mass spectroscopy [13]. Spleen phosphodiesterase was from Worthington Biochemical (Lakewood, NJ), nuclease P1 was from Yamasa Shoyu Co. (Choshi, Japan), and [γ-32 P]-ATP and T4 polynucleotide kinase (T4 PNK) were from Amersham (Piscataway, NJ).…”
Section: Chemicalsmentioning
confidence: 99%
“…As a major reaction, Acr reacts with deoxyguanosine (dG) in DNA to produce two pairs of diastereomeric adducts (Scheme 1A): (6R/S)-3-(2'-deoxyribos-1'-yl)-5,6,7,8-tetrahydro-6-hydroxypyrimido[1,2-α] purine-10(3H)one (α-OH-Acr-dG) and (8R/S)-3-(2'-deoxyribos-1'-yl)-5,6,7,8-tetrahydro-8-hydroxypyrimido[1,2-α]purine-10(3H)one (γ-OH-Acr-dG) [11,12]. A highly sensitive HPLCbased 32 P-postlabeling method was developed earlier for the detection of Acr-dG in tissue DNA [13]. Using this method, Acr-dG adducts were detected in tissue of untreated rodents and humans as background lesions in DNA [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10]. Acrolein-induced DNA adducts have been characterized in vitro (11)(12)(13)(14) and quantified in vivo in various organs of experimental animals and humans (9,10,15,16). A recent in vitro study has shown preferential formation of acrolein-DNA adducts at lung cancer mutational hotspots in the p53 tumor suppressor gene in normal human bronchial epithelial cells and lung fibroblasts (17).…”
Section: Introductionmentioning
confidence: 99%